Evaluating The Relationship Between Human Resources Management Practices And Career Development For Employees In The Ministry Of Higher Education In The State Of Kuwait (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This study aimed to evaluate the relationship between human resources management practices in the Ministry of Higher Education in the State of Kuwait, and the career development of its employees. To achieve the objectives of the study, the descriptive analytical method and the questionnaire were used as a tool for collecting data, from the study sample, which consisted of (279) employees. Workers in the Ministry of Higher Education in the State of Kuwait. The results of the study concluded that the reality of applying human resources management practices in the Ministry of Higher Education in the State of Kuwait in general was high, and the order of application of human resources management practices was descending from most to least applied to The following figure: Human resources planning is in first place, training and development is second, recruitment and recruitment is third, compensation and incentives are fourth, and performance evaluation is fifth. The results also showed an increase in the reality of career development for employees in the Ministry of Higher Education in the State of Kuwait, and that there are no statistically significant differences when The level of significance (α ≤ 0.05) between the responses of the sample members about the reality of applying human resources management practices in the Ministry of Higher Education in the State of Kuwait, or about the level of career development for its employees, which is attributed to the variables of gender and the number of years of experience. Finally, it was found that there is A significant correlation at the significance level (α ≤ 0.05) between human resources management practices and career development for employees in the Ministry of Higher Education in the State of Kuwait.